Nucleotide variations of WRKY70 gene sequence related to Huanglongbing resistance in citrus - Nugroho, Kristianto; Purwito, Agus; Sukma, Dewi; Kosmiatin, Mia; Santoso, Tri Joko; Reflinur, Reflinur; Mastur, Mastur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Huanglongbing, inflicted by Candidatus Liberibacter asiaticus in Asia region, is a destructive disease affecting citrus productions worlwide. Several studies have identified resistance genes that play essential roles in the citrus defense system against this pathogen. The goals of this study were to design the specific gene primers from the WRKY70 gene sequence and analyze the nucleotide variations and genetic diversity among several citrus genotypes. Genomic DNA from nine citrus genotypes were amplified using WRKY70-specific gene primers and the products of PCR were sent to Sanger sequencing, while the sequences of the other 12 genotypes were collected from Citrus Genome Database. The results revealed a total of 282 nucleotide variations which consisted of 157 SNPs, 28 insertions, and 97 deletions, were identified in the WRKY70 gene fragment sequence. There were three notable SNPs detected, with only one SNP [C/T] in first intron area at the position of 524 bp downstream from START codon that showed its ability to distinguish between susceptible and tolerant/resistant citrus genotypes. The phylogenetic analysis also revealed the clearly separation among citrus genotypes in two main clusters. The discovery of this SNP is useful for designing a functional marker as a screening tool in citrus breeding program in the future.